Barriers To Implementing the 5s Method According to Employees of a Production Company - Results of The Survey - Damian OSTROWSKI; Agnieszka PIASECKA – GLUSZAK (Communications of International Proceedings, 2021)
The implementation of the theoretical principles and values of lean management is based on the use of practical tools (so-called lean tools). One of the most frequently implemented methods involves the 5S. 5S is a simple and effective method of eliminating waste and organising the workplace. It can be implemented in production processes, office processes, customer service processes, etc. In its simplicity of implementation and effectiveness, it generates benefits very quickly, however, difficulties arise when an organisation wants to maintain a particular implementation standard in the long term. In this paper, the results of the research confirm the general pattern that for many organisations, maintaining a long-term approach to the 5S method is problematic. The main barriers identified by employees include: an emphasis on short-term gains, the lack of adequate support from management, and the lack of a general atmosphere that encourages the implementation of 5S. Without 5S there is no possibility to implement the concept of lean management, so the management should take special care of the success of the implementation of this method. This paper continues considerations on the implementation of 5S in the organisation.
Keywords: 5S; lean management; implementation barriers